The Impact of Net Interest Income and ESG on Bank Performance - Hartini Pop Koapaha (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study examines the relationship between net-interest income, ESG performance, and bank performance using a multiple regression analysis on a panel dataset of publicly traded banks in the United States. The independent variables are net interest income and Refinitiv ESG score, while the dependent variable is Tobin's Q. The control variables are bank size (proxied by total assets) and risk (NPL to total loans). The results of the linear regression model were significant, indicating that approximately 40.78% of the variance in Tobin's Q is explainable by LNNII, ESG, LNTA, and NPLTL. ESG performance is found to be a significant predictor of bank performance, while net interest income has a mixed relationship with bank performance. Effective credit risk management is essential for banks to maintain their financial performance and sustainability. The findings of this study have important implications for bank managers, regulators, and policymakers who are responsible for promoting sustainable banking practices and ensuring the stability and resilience of the banking sector.